PetR’Us management system for My Pets’ Bowl / Aida Diana Mohd Shah - Mohd Shah, Aida Diana (2017)
The purpose of this project is to solve the problem faced by Encik Aiman, the owner of My Pets’ Bowl. The problem is that been facing is the tasks are being done in the store are be made manually and without the help of any computerized system. On the other hand, the process of checking the boarding availability and appointment book is very tedious and time consuming. On the other hand, customer finds it difficult to keep up to date with the latest announcement of the store as the old news being overshadowed by the latest news. By developing a web-based system named PetR’Us that is able to assist Encik Aiman to manage the management of the store and reservation for pets boarding, grooming, mating and treatment services. This system also able to store the reservation data for boarding, treatment, grooming and mating that can be stored neatly and accordingly for easier future references. Besides that, the system also provides advertisement management in order to assist Encik Aiman to manage the advertisement sections. This system might be able to reduce the problem that occurring in store by using the reservation system.